Study of Kinetics, Equilibrium and the Influence of Steric Effects on Proton-Transfer in the Reactions of 2, 2, 4- and 2, 6- Substituted Anilines with 2-Phenoxy-3,5-dinitropyridine in DMSO - Basim H. Asghar (E-Journal of Chemistry)
Kinetic and equilibrium results for the reactions of 2-phenoxy-3,5-dinitropyridine (1), with a series of 2, 2, 4- and 2, 6- substituted anilines (2a-f), in the presence of DABCO in DMSO are reported. The reactions yield the 2-anilino derivatives (5), without the accumulation of intermediates. Kinetics studies are compatible with a two-step mechanism involving initial nucleophilic attack by amine at the ring carbon substituted by phenoxy group followed by either base-catalyzed or uncatalyzed conversion to the product. The base-catalyzed pathway is likely to involve rate-limiting proton-transfer from the zwitterionic intermediate to base. This work indicates a steric effect to proton transfer in reactions involving 2, 6-disubstituted anilines. The results were compared with those for reactions of 1, 3, 5-trinitrobenzene with anilines.